TiO2-decorated porous carbon nanofiber interlayer for Li–S batteries - Yanilmaz, Meltem (Royal Society of Chemistry (RSC), 2020)
Lithium–sulfur (Li–S) batteries are the most promising energy storage systems owing to their high energy density.
Keywords: Chemistry